Features of Role and Innovative Behavior in Relation to Work Experience - Avdeeva A.P; Ermolaeva M.V; Kokueva Zh.M; Lubovsky D. (Moscow State University of Psychology and Education, 2022)
The authors have shown the relevance and justified the need to study the relationship between the types of innovative and role behavior of project team members and students who have no experience in group design. The purpose of the research is to study the correlation between the types of role behavior in a team and innovative behavior among managers with experience in project teams and students without such experience. In the 1st part of the study, a group of employees of industrial enterprises aged from 19 to 40 years and with work experience from 6 months to 22 years (n=45) took part, in the 2nd part of the study - undergraduate students in the direction of "Innovation" (n=20, age 20-22 years) and working managers with experience (n=30, age 21-41 years). The main hypothesis of the study is the assumption of significant discrepancies among students between their characteristic types of role and innovative behavior and their ideas about what team roles and types of innovative behavior are characteristic of them. In the first part of the study, using questionnaires of role behavior in a team and innovative behavior, the types of role and innovative behavior and combinations of types of role and innovative behavior of project team members were studied. The complementarity in frequently occurring combinations of role and innovative behavior of managers of innovative projects is revealed; such complementarity is absent in students. The results of the second part of the study show that employees with experience have the most widespread types of innovative behavior that provide incremental innovations, students have radical innovations. Among employees with experience, team roles of a social orientation are significantly more widespread than among students, among students - action roles, significant discrepancies between the types of role behavior according to questionnaires and those that students choose according to descriptions as characteristic of them were revealed. Students, in comparison with employees of enterprises, overestimate their readiness for intellectual roles in the team. The practical significance of the obtained results is shown, prospects for further research are outlined.